Update on guidelines for management of hypercholesterolemia. (October 2012) - Mannu, Gurdeep S; Zaman, M Justin S; Gupta, Abhaya; Rehman, Habib U; Myint, Phyo K
Coronary heart disease (CHD) is a leading cause of morbidity and mortality globally. Hypercholesterolemia is one of the major risk factors for CHD. With the increase in aging populations and progressively sedentary lifestyles, the global burden of CHD is likely to increase in the future despite better preventive strategies. It is vitally important to manage hypercholesterolemia effectively because it is a modifiable risk factor. At present, there are several guidelines with differences in recommendations. In this paper the authors present an update on the guidelines on hypercholesterolemia management. The authors have systematically reviewed guidelines in hypercholesterolemia management and discussed a pragmatic approach to follow the most recent guidelines including guidance from NICE in the primary care setting.